The radio detection and accretion properties of the peculiar nuclear transient AT 2019avd. Issue 2 (11th January 2023) - Wang, Yanan; Baldi, Ranieri D; del Palacio, Santiago; Guolo, Muryel; Yang, Xiaolong; Zhang, Yangkang; Done, Chris; Castro Segura, Noel; Pasham, Dheeraj R; Middleton, Matthew; Altamirano, Diego; Gandhi, Poshak; et al.
ABSTRACT: AT 2019avd is a nuclear transient detected from infrared to soft X-rays, though its nature is yet unclear. The source has shown two consecutive flaring episodes in the optical and the infrared bands, and its second flare was covered by X-ray monitoring programs. During this flare, the UVOT/ Swift photometries revealed two plateaus: one observed after the peak and the other one appeared ∼240 d later. Meanwhile, our NICER and XRT / Swift campaigns show two declines in the X-ray emission, one during the first optical plateau and one 70–90 d after the optical/UV decline. The evidence suggests that the optical/UV could not have been primarily originated from X-ray reprocessing. Furthermore, we detected a timelag of ∼16–34 d between the optical and UV emission, which indicates the optical likely comes from UV reprocessing by a gas at a distance of 0.01–0.03 pc. We also report the first VLA and VLBA detection of this source at different frequencies and different stages of the second flare. The information obtained in the radio band – namely a steep and a late-time inverted radio spectrum, a high brightness temperature and a radio-loud state at late times – together with the multiwavelength properties of AT 2019avd suggests the launching and evolution of outflows such as disc winds or jets. In conclusion, we propose that after the ignition of black hole activity in the first flare, a super-Eddington flaring accretion disc formed and settled to a sub-Eddington state by the end of the second flare, associated with a compact radio outflow.